Dissociation in the letter to the Galatians - Vorster, Johannes N. (1992)
From the perspective of modern rhetoric, this article proposes the technique of dissociation as an alternative to approaches in which the antithesis featured predominantly. The technique of dissociation is applied, not only to the person of Paul, but also to the related question of what being a real Jew entails. It is indicated that the technique of dissociation should be seen in relationship to the pragmatic argument. Seen from this perspective, the letter to the Galatians is an attempt at the confirmation of status.
Keywords: Dissociation; New Testament Bible; Rhetorical criticism; Galatians; Theology; Christianity